(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
In the article entitled “Application of the Modern Method of “Flipped Classroom” in the Process of Teaching Literature,” we aimed to highlight the distinctive features of this teaching method, shaped by the nature of the subject matter, the ideological and aesthetic framework, and the number of instructional hours allocated. We examined several approaches to implementing the method, aligning with its core principles. The essence of the flipped classroom method and its fundamental teaching principles were explored, with particular emphasis on its advantages, which stemmed from its unique characteristics and the specific educational objectives it served. By applying different approaches within the “Flipped Classroom” framework, we underscored the particularities of teaching certain literary works. This method proved to be an effective tool for analyzing literature, as it allowed for extended in-class discussions on key topics introduced in teacher-prepared video lessons. This, in turn, facilitated more in-depth analysis. Several advantages of the method were highlighted, including the ability for students to rewatch video lessons multiple times at home, reviewe and reinforce previous lessons as needed, engage in pre-class discussions with peers and teachers, and systematically organize new information. These elements contribute to a deeper and more comprehensive understanding of the material.